Relational cutoff and its role in protecting the self in social contexts - Koçyiğit, Metin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
The present study aimed to explore defensive features of relational cutoff in social contexts. Relational cutoff was conceptualized as stopping speaking to another person for a variable length of time, because of seemingly unresolvable conflict between intimates. Relational cutoff was investigated conditions in which the participants had the role of the offended or the offender in the conflict. The data were collected from 12 participants including 6 university students and 6 adults through a semi-structured one time interview. Grounded theory (Charmaz, 2006) was applied to analyze the interviews. It appeared that relational cutoff involved both intrapsychic and interpsychic processes, beginning with a narcissistic injury, followed by counteractions, relational evaluation. Relatioanal cutoff ended with forgiveness, resolved partially or stayed as unresolved. The results revealed that relational cutoff can be considered as having defensive elements consisting of avoiding overwhelming unpleasant emotions and having an unconscious motivation to protect the cohesiveness of self and self-esteem. The findings were discussed through the classical and the relational psychoanalytical perspectives by taking into consideration of the norms in the Turkish culture. Generational and gender differences in experiencing relational cutoff were also debated. Limitations and implications of the present study were also reviewed.
Keywords: Life cycle, Human.